optical fiber
By adding chlorine to the core of the optical fiber and controlling the fluorine concentration in the cladding, the problem of increasing transmission loss caused by glass defects during the optical fiber manufacturing process is solved, further reducing the transmission loss of the optical fiber and stability of optical characteristics are achieved.
Patent Information
- Application Number
- CN202080064427.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-10-31
- Filing Date
- 2020-10-20
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2040-10-20
AI Technical Summary
During the optical fiber manufacturing process, the diffusion of the alkali metal element group causes the structural bonds of the glass to be cut off, resulting in glass defects, thereby increasing the transmission loss of the optical fiber. The prior art is difficult to further reduce transmission losses by optimizing the fluorine concentration of the cladding.
By adding chlorine to the core of the optical fiber and controlling the average concentration of fluorine in the cladding is below 1.2% (or below 1.4%), to ensure that the relative refractive index difference of the core is above 0.00% and below 0.15% (or above -0.15% and below 0.05%), thereby reducing transmission losses.
The optical fiber transmission loss is further reduced, ensuring the communication capacity and optical characteristics of the optical fiber.
Smart Images

Figure CN114402240B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to an optical fiber. This application claims priority to Japanese Application No. 2019-198768 filed on October 31, 2019, and all the contents described in the Japanese Application are cited. Background Art
[0002] Generally, if the core of silica-based glass contains an alkali metal element or an alkaline earth metal element, the viscosity of the core is reduced and the rearrangement of the glass is promoted when an optical fiber preform is drawn to produce an optical fiber. This can reduce the transmission loss of the optical fiber caused by Rayleigh scattering. Hereinafter, both the alkali metal element and the alkaline earth metal element are referred to as the "alkali metal element group".
[0003] Patent Document 1 discloses an optical fiber in which an alkali metal element is doped in the core. In this optical fiber, the transmission loss is reduced by optimizing the alkali metal element concentration in the core and the fluorine concentration in the cladding.
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent document 1: U.S. Patent No. 5,146,534. Summary of the invention
[0007] An optical fiber according to one embodiment of the present invention is formed of silica-based glass. The optical fiber has a core including a central axis and a cladding surrounding the core. The refractive index of the core is greater than the refractive index of the cladding. The core contains chlorine and contains one or more elements of an element group consisting of alkali metal elements and alkaline earth metal elements. The relative refractive index difference of the core based on the refractive index of pure silica is greater than 0.00% and less than 0.15%. The average concentration of fluorine in the cladding is less than 1.2% by mass.
[0008] An optical fiber according to another embodiment of the present invention is formed of silica-based glass. The optical fiber has a core including a central axis and a cladding surrounding the core. The refractive index of the core is greater than the refractive index of the cladding. The core contains chlorine and contains one or more elements of an element group consisting of alkali metal elements and alkaline earth metal elements. The relative refractive index difference of the core based on the refractive index of pure silica is greater than -0.15% and less than 0.05%. The average concentration of fluorine in the cladding is less than 1.4% by mass. BRIEF DESCRIPTION OF THE DRAWINGS
[0009] Figure 1 is a cross-sectional view of an optical fiber according to an embodiment.
[0010] Figure 2 Yes Description Figure 1Flow chart of a method for manufacturing an optical fiber.
[0011] Figure 3 This is a graph showing the relationship between the average fluorine concentration of the cladding of optical fibers 1 to 9 and the transmission loss at a wavelength of 1550 nm.
[0012] Figure 4 This is a graph showing the relationship between the average fluorine concentration of the cladding of the optical fibers 10 to 18 and the transmission loss at a wavelength of 1550 nm. DETAILED DESCRIPTION
[0013] [Problems to be Solved by the Invention]
[0014] The alkali metal element group added to the core center in the state of the optical fiber preform will diffuse during drawing. Therefore, in the case where the core containing the alkali metal element group does not contain chlorine (or the chlorine content is low), the bonds of the glass molecular structure are cut and glass defects are generated. Therefore, in the obtained optical fiber, the transmission loss caused by the glass defects increases. In the case where the core contains a sufficient amount of chlorine, the chlorine combines with the glass defects to suppress the generation of glass defects. As a result, the increase in transmission loss caused by the glass defects is suppressed.
[0015] In Patent Document 1, it is believed that the alkali metal element concentration of the core and the fluorine concentration of the cladding will affect the transmission loss. It can be seen from this that the fluctuation of the fluorine concentration of the cladding will also affect the transmission loss. That is, the transmission loss can be reduced by optimizing the fluorine concentration of the cladding. However, once the refractive index of the core is determined, in order to control the optical properties such as the cut-off wavelength within a certain range, the refractive index of the cladding has to be set to the determined refractive index. Therefore, it is believed that there is no substantial degree of freedom in the design of the fluorine concentration of the cladding. Based on such considerations, it is difficult to seek a further reduction in transmission loss by optimizing the fluorine concentration of the cladding.
[0016] Therefore, an object of the present invention is to provide an optical fiber capable of further reducing transmission loss.
[0017] [Effects of the invention]
[0018] According to the present invention, it is possible to provide an optical fiber capable of further reducing transmission loss.
[0019] [Description of Embodiments of the Invention]
[0020] First, the embodiments of the present invention are listed for explanation. An optical fiber of one embodiment is formed of silica-based glass. The optical fiber has a core including a central axis and a cladding surrounding the core. The refractive index of the core is greater than the refractive index of the cladding. The core contains chlorine and contains one or more elements of an element group consisting of alkali metal elements and alkaline earth metal elements. The relative refractive index difference of the core based on the refractive index of pure silica is greater than 0.00% and less than 0.15%. The average concentration of fluorine in the cladding is less than 1.2% by mass.
[0021] In the optical fiber of the above embodiment, the average concentration of fluorine in the cladding is 1.2% by mass or less, and thus the transmission loss can be further reduced.
[0022] The average fluorine concentration in the cladding may be 1.1% by mass or less. In this case, the transmission loss can be further reduced more reliably.
[0023] The average fluorine concentration in a region of the cladding whose distance from the central axis is 1 to 2 times the radius of the core may be 1.2% or less by mass. In this case, the transmission loss can be further reduced.
[0024] The average fluorine concentration in a region of the cladding whose distance from the central axis is 1 to 2 times the radius of the core may be 1.1% or less by mass. In this case, further reduction in transmission loss can be achieved more reliably.
[0025] The optical fiber of another embodiment is formed of silica-based glass. The optical fiber has a core including a central axis and a cladding surrounding the core. The refractive index of the core is greater than the refractive index of the cladding. The core contains chlorine and contains one or more elements of an element group consisting of alkali metal elements and alkaline earth metal elements. The relative refractive index difference of the core based on the refractive index of pure silica is greater than -0.15% and less than 0.05%. The average concentration of fluorine in the cladding is less than 1.4% by mass.
[0026] In the optical fiber according to the above-mentioned other embodiment, the average concentration of fluorine in the cladding is 1.4% by mass or less, and thus the transmission loss can be further reduced.
[0027] The average fluorine concentration in the cladding may be 1.3% by mass or less. In this case, the transmission loss can be further reduced more reliably.
[0028] The average fluorine concentration in a region of the cladding whose distance from the central axis is 1 to 2 times the radius of the core may be 1.4% or less by mass. In this case, the transmission loss can be further reduced.
[0029] The average fluorine concentration in a region of the cladding whose distance from the central axis is 1 to 2 times the radius of the core may be 1.3% or less by mass. In this case, further reduction in transmission loss can be achieved more reliably.
[0030] The difference between the maximum value and the minimum value of the residual stress of the optical fiber may be 10 MPa or more. In this case, it is possible to adjust the characteristics such as increasing the cutoff wavelength of the optical fiber.
[0031] The effective cross-sectional area of the optical fiber can be 70 μm 2 Above and 90μm 2 In this case, communication capacity can be ensured.
[0032] The outer diameter of the cladding is greater than or equal to 124 μm and less than or equal to 126 μm, and the residual stress of the optical fiber can be at a maximum value in a region where the distance from the central axis is greater than or equal to 20 μm and less than or equal to 55 μm. In this case, the residual stress in this region is treated as a tensile stress, thereby increasing the cutoff wavelength of the optical fiber. In addition, in the present invention, when the residual stress is a tensile stress, the residual stress is represented by a "positive value", and when the residual stress is a compressive stress, the residual stress is represented by a "negative value". The "magnitude of the residual stress" is set based on this definition.
[0033] The outer diameter of the cladding is 124 μm to 126 μm, and in the optical fiber, the minimum value of the residual stress in the region where the distance from the central axis is 50 μm to 62.5 μm can be 10 MPa or less. In this case, the residual stress in the region closer to the inside than the region is made tensile stress, thereby increasing the cutoff wavelength of the optical fiber.
[0034] The average concentration of one or more elements in the element group consisting of alkali metal elements and alkaline earth metal elements in the core can be 0.2 ppm or more and 200 ppm or less in terms of mass fraction. In this case, since it is 0.2 ppm or more, the Rayleigh scattering loss can be fully reduced. Since it is 200 ppm or less, the increase in loss caused by potassium concentration fluctuation can be suppressed.
[0035] The element group may consist of sodium, potassium, cesium and calcium. In this case, any one of the elements can reduce the viscosity of the core and reduce Rayleigh scattering losses.
[0036] [Details of the embodiments of the present disclosure]
[0037] Below, refer to the attached Figure 1The specific examples of the optical fiber of the present invention are described. In addition, the present invention is not limited to these examples, but is represented by the scope of the claims, and is intended to include the meaning equivalent to the scope of the claims and all changes within the scope. In the description of the drawings, the same elements are marked with the same symbols, and repeated descriptions are omitted.
[0038] Figure 1 is a diagram showing a cross-sectional view of an optical fiber according to an embodiment. Figure 1 As shown, the optical fiber 1 of this embodiment includes a core 10 including a central axis C, a cladding 20 surrounding the core 10, and a resin coating (not shown) surrounding the cladding 20. The cladding 20 includes a first cladding 21 surrounding the core 10 and a second cladding 22 surrounding the first cladding 21. Figure 1 The cross-sectional view of FIG. 1 shows a cross-section perpendicular to the central axis C. The optical fiber 1 is formed of silica-based glass. The refractive index of the core 10 is greater than the refractive index of the cladding 20. The effective cross-sectional area of the optical fiber 1 is, for example, 70 μm 2 Above and 90μm 2 The difference between the maximum value and the minimum value of the residual stress of the optical fiber 1 is, for example, 10 MPa or more.
[0039] The core diameter (diameter of the core 10) is, for example, 8 μm or more and 15 μm or less. The first cladding diameter (outer diameter of the first cladding 21) is, for example, 20 μm or more and 60 μm or less. The second cladding diameter (outer diameter of the second cladding 22) is, for example, 124 μm or more and 126 μm or less. In the present embodiment, the second cladding diameter is also the cladding diameter (outer diameter of the cladding 20). In the present embodiment, the core diameter is 9 μm or more and 10 μm or less, and the cladding diameter is 125 μm.
[0040] The core 10 contains chlorine (Cl) and fluorine (F). The core 10 also contains one or more elements of an element group consisting of an alkali metal element and an alkaline earth metal element (hereinafter referred to as "alkali metal element group"). The alkali metal element group can be composed of, for example, sodium (Na), potassium (K), cesium (Cs) and calcium (Ca). In this case, the alkali metal element group contains sodium, potassium and cesium as alkali metal elements, and contains calcium as an alkaline earth metal element.
[0041] The relative refractive index difference of the core 10 based on the refractive index of pure silica may be, for example, 0.00% to 0.15%, or 0.05% to 0.07%. In this case, the average fluorine concentration (F) of the cladding 20 is ave ) is, for example, 0.55% or more and 1.2% or less in terms of mass fraction. This can further reduce the transmission loss. The average fluorine concentration (F ave ) can be, for example, 0.60% or more and 1.1% or less in terms of mass fraction. This can more reliably achieve a further reduction in transmission loss.
[0042] The relative refractive index difference of the core 10 based on the refractive index of pure silica may be, for example, not less than -0.15% and not more than 0.05%, or not less than -0.08% and not more than -0.05%. In this case, the average fluorine concentration (F ave ) is, for example, 1.0% or more and 1.4% or less in terms of mass fraction. This can further reduce the transmission loss. The average fluorine concentration (F ave ) can be, for example, 1.1% or more and 1.3% or less in terms of mass fraction. This can more reliably achieve a further reduction in transmission loss.
[0043] Here, the average fluorine concentration (F ave ) can be defined as the average fluorine concentration in the entire cladding area, or can be defined as the average fluorine concentration in the area of the cladding 20 where the distance from the central axis is more than 1 times and less than 2 times the radius of the core 10. In the latter case, the average fluorine concentration of the cladding 20 refers to the average value of the fluorine concentration in the range of the cladding 20 from the core diameter to twice the core diameter that is closer to the core, and can be calculated as follows (1). F(r) refers to the local fluorine concentration, and a refers to the radius of the core 10.
[0044] [Mathematical formula 1]
[0045]
[0046] The average concentration of the elements of the alkali metal group in the core 10 is 0.2 ppm or more and 200 ppm or less in terms of mass fraction. For example, when the core 10 contains potassium, the average K concentration of the core 10 can be calculated as shown in the following formula (2). K(r) refers to the local K concentration, and a refers to the radius of the core 10.
[0047] [Mathematical formula 2]
[0048]
[0049] Figure 2 Yes Description Figure 1 Flow chart of the method for manufacturing an optical fiber. An example of specific conditions is also described in the following description. The optical fiber is manufactured by sequentially undergoing a preparation step (step S1), an addition step (step S2), a diameter reduction step (step S3), an etching step (step S4), a solidification step (step S5), a stretching and grinding step (step S6), a rod sleeve hot melting step (step S7), an OVD step (step S8), and a drawing step (step S9).
[0050] In the preparation process (step S1), a glass tube of silicon-based glass for diffusing an alkali metal element group (dopant) is prepared. A silicon-based glass cylinder as a raw material of the glass tube contains a certain concentration of chlorine and a certain concentration of fluorine, and the concentration of other dopants and impurities is less than 10 ppm by mass fraction. The outer diameter of the glass tube of silicon-based glass is greater than 30 mm and less than 40 mm, and the inner diameter is greater than 15 mm and less than 25 mm.
[0051] In the adding process (step S2), potassium (K) element is added to the inner surface of the glass tube of the silica-based glass as a dopant of the alkaline earth metal group. As a raw material, potassium bromide (KBr) of more than 6g and less than 10g is used. The raw material is heated to a temperature of more than 750°C and less than 850°C by an external heat source to generate raw material vapor. While the raw material vapor is introduced into the interior of the glass tube of the silica-based glass together with a carrier gas composed of oxygen with a flow rate of 1SLM (converted to a volume of 1 liter / minute at 0°C and 1013hPa), the glass tube of the silica-based glass is heated from the outside using a hydrogen-oxygen burner so that the outer surface of the glass tube of the silica-based glass reaches a temperature of more than 1600°C and less than 1800°C. At this time, the burner is moved horizontally at a speed of more than 30mm / min and less than 60mm / min, and the heating is performed for a total of more than 10 back and forth and less than 15 back and forth, so that the K element is diffused and added to the inner surface of the glass tube of the silica-based glass.
[0052] In the diameter reduction process (step S3), the glass tube of silica-based glass to which K is added is reduced in diameter. At this time, while oxygen is flowed into the interior of the glass tube of silica-based glass at a rate of 0.5 SLM or more and 1.0 SLM or less, the glass tube of silica-based glass is heated by an external heat source so that the outer surface of the glass tube of silica-based glass reaches 2000° C. or more and 2300° C. or less. The external heat source is transversely heated for a total of 6 or more and 10 or less times to reduce the diameter of the silica glass tube to an inner diameter of 3 mm or more and 6 mm or less.
[0053] In the etching process (step S4), the inner surface of the glass tube of the silica-based glass is etched. At this time, a mixed gas of SF6 (0.2 SLM or more and 0.4 SLM or less) and chlorine (0.5 SLM or more and 1.0 SLM or less) is introduced into the interior of the silica glass tube, while the silica glass tube is heated by an external heat source for vapor phase etching. Thus, the inner surface of the tube containing impurities added together with the target dopant at a high concentration can be removed, and the impurities can be removed.
[0054] In the solidification process (step S5), the glass tube of the silica-based glass is solidified. In the solidification process, a mixed gas of oxygen (0.1 SLM or more and 0.5 SLM or less) and He (0.5 SLM or more and 1.0 SLM or less) is introduced into the interior of the silica glass tube 30, and the absolute pressure in the silica glass tube is reduced to less than 97 kPa while the surface temperature is made to be more than 2000°C and less than 2300°C to solidify the silica glass tube. The core (outer diameter of 20 mm or more and 30 mm or less) is obtained by the solidification. A core layer free of alkali metal elements may also be provided to the outside of the rod by a known method such as an OVD (Outside vapor deposition) method or a sleeve hot melt method.
[0055] In the stretching and grinding step (step S6), the core is stretched to a diameter of 20 mm to 25 mm, and the outer peripheral portion of the core is ground to a diameter of 15 mm to 20 mm. This portion becomes the core of the optical fiber.
[0056] In the plunger tube heat melting step (step S7), the first cladding portion is provided outside the core portion. In this case, the plunger tube heat melting method is used, that is, the core portion is inserted into the glass tube of the silica-based glass to which fluorine is added, and the two are heated by an external heat source to be integrated. As a result of the synthesis by the plunger tube heat melting method, the moisture content of the core portion and the first cladding portion near it can be suppressed to a sufficiently low level.
[0057] In the OVD process (step S8), after the rod formed by integrating the core and the first cladding is stretched to a predetermined diameter, a second cladding containing fluorine is synthesized on the outside of the rod by OVD to produce an optical fiber preform.
[0058] In the drawing process (step S9), the optical fiber preform manufactured by the above optical fiber preform manufacturing method can be drawn to obtain an optical fiber. In this process, the optical fiber preform is heated in a drawing furnace to draw the optical fiber, and then the optical fiber is slowly cooled in a slow cooling furnace provided downstream of the drawing furnace. The drawing tension and the temperature of the slow cooling furnace are adjusted so that each optical fiber preform satisfies the condition that the cutoff wavelength is less than 1530nm and the transmission loss is minimized.
[0059] In the optical fiber 1, the cutoff wavelength is less than 1530 nm. In order to satisfy this condition, the refractive index of the optical fiber 1 is changed from the refractive index of the optical fiber preform by the following method 1 or method 2. Method 1 is a method in which the residual stress inside the optical fiber 1 is changed by changing the drawing tension in the drawing process, and the refractive index of the optical fiber 1 is changed accordingly. Method 2 is a method in which the outermost peripheral portion of the glass is heated by slow cooling in the drawing process, thereby changing the residual stress inside the optical fiber 1 and the refractive index of the optical fiber 1 is changed accordingly. In particular, in method 2, compared with the optical fiber that is not slow cooled during drawing, method 2 can further increase the tensile stress of the portion where the tensile stress remains by reducing the residual stress in the outermost peripheral portion, so that the cutoff wavelength can be adjusted (increased) as a result. In this way, in the drawing process, by changing the refractive index to adjust the optical design, the fluorine concentration originally contained in the cladding portion of the optical fiber preform can be reduced. Therefore, it is possible to achieve both the reduction of transmission loss caused by the fluctuation of the fluorine concentration of the cladding 20 and the desired optical characteristics.
[0060] By the above method 1, the residual stress of the optical fiber 1 becomes a maximum value in a region where the distance from the central axis C is, for example, 20 μm or more and 55 μm or less. The range of this maximum value is, for example, 5 MPa or more and 50 MPa or less. In the optical fiber 1, by setting a portion where the residual stress is a tensile stress in a region where the distance from the central axis C is 20 μm or more and 55 μm or less, the cut-off wavelength can be increased. By the above method 2, the minimum value of the residual stress in the region where the distance from the central axis C is 50 μm or more and 62.5 μm or less is, for example, 10 MPa or less, but it can also be 0 MPa or less. That is, the residual stress can also be a compressive stress. In addition, although the distance from the outer peripheral surface of the cladding 20 to the central axis C is, for example, 62.5 μm, as long as it is 50 μm or more and 75 μm or less, the design adjustment can be performed in the same way. In the optical fiber 1 , the cutoff wavelength can be increased by making the residual stress a tensile stress in a region closer to the central axis C than a region at a distance of 50 μm to 62.5 μm.
[0061] Table 1 is a table summarizing the parameters of the nine types of optical fibers 1 to 9 that were manufactured and evaluated. In this table, the average K concentration (K) of the core of each optical fiber 1 to 9 is shown. ave ), transmission loss at wavelength 1550nm (α 1.55 ), core diameter, cut-off wavelength, effective cross-sectional area (A eff ) and the average fluorine concentration of the cladding (F ave). In optical fibers 1 to 9, the relative refractive index difference of the core based on the refractive index of the cladding varies between 0.25% and 0.45%. In the manufacture of optical fibers 1 to 9, as described above, the drawing tension and the temperature of the annealing furnace are adjusted so that each optical fiber preform satisfies the condition that the cutoff wavelength is less than 1530nm, while also minimizing the transmission loss. The relative refractive index difference of the core based on the refractive index of pure silica is greater than 0.05% and less than 0.07%. The concentration is measured by, for example, polishing the sample surface and using EPMA (Electron Probe Micro Analyzer). At this time, the acceleration voltage is set to 20kV, the probe beam diameter is set to less than 1μm, and the measurement interval is set to less than 100nm.
[0062] [Table 1]
[0063]
[0064] Figure 3 Graph showing the relationship between the average fluorine concentration of the cladding of optical fibers 1 to 9 and the transmission loss at a wavelength of 1550 nm. Figure 3 As shown in FIG. 1 , it was confirmed that the transmission loss tended to be the lowest when the average fluorine concentration of the cladding was around 0.8% by mass.
[0065] Table 2 is a table summarizing the parameters of the nine types of optical fibers 10 to 18 manufactured and evaluated. In this table, the average K concentration of the core, the transmission loss at a wavelength of 1550nm, the core diameter, the cutoff wavelength, the effective cross-sectional area, and the average fluorine concentration of the cladding are shown for optical fibers 10 to 18, respectively. In optical fibers 10 to 18, the relative refractive index difference of the core based on the refractive index of the cladding varies between 0.25% and 0.45%. In the manufacture of optical fibers 10 to 18, as described above, the drawing tension and the temperature of the quenching furnace are also adjusted so that each optical fiber preform satisfies the condition that the cutoff wavelength is less than 1530nm, while also minimizing the transmission loss. The relative refractive index difference of the core based on the refractive index of pure silica is greater than -0.08% and less than -0.05%. The concentration is measured by, for example, polishing the sample surface and using EPMA (Electron Probe Micro Analyzer). At this time, the acceleration voltage was set to 20 kV, the probe beam diameter was set to 1 μm or less, and the measurement interval was set to 100 nm or less.
[0066] [Table 2]
[0067]
[0068] Figure 4: is a graph showing the relationship between the average fluorine concentration of the cladding of optical fibers 10 to 18 and the transmission loss at a wavelength of 1550 nm. Figure 4 As shown, it was confirmed that the transmission loss tended to be the lowest when the average fluorine concentration of the cladding was around 1.2% by mass.
[0069] Table 3 is a table summarizing the parameters of the five types of optical fibers 19 to 23 that were manufactured and evaluated. In this table, the average K concentration (K) of the core of each of the optical fibers 19 to 23 is shown. ave ), transmission loss at wavelength 1550nm (α 1.55 ), core diameter, cut-off wavelength, effective cross-sectional area (A eff ), the average fluorine concentration of the cladding (F ave ) and microbend loss (μ bending loss). The microbend loss is measured by the mesh bobbin test specified in IEC TR62221. In optical fibers 19 to 23, the effective cross-sectional area is increased from 80 μm 2 Changed to 124 μm 2 The relative refractive index difference of the core based on the refractive index of the cladding varies between 0.25% and 0.45%. When the effective cross-sectional area exceeds 90 μm 2 When the microbend loss increases to more than 0.4 dB / km, a trend is confirmed.
[0070] [Table 3]
[0071]
[0072] The transmission loss also depends on the concentration of the alkali metal element group contained in the core. However, in the optical fibers 1 to 23, since the concentration of the alkali metal element group is uniformly set to 40 ppm by mass, it is considered that the influence is small.
[0073] Description of Reference Numerals
[0074] 1…Fiber Optic
[0075] 10…Core
[0076] 20…Clad
[0077] 21…1st cladding
[0078] 22…Second cladding
[0079] C…Center axis
Claims
1. An optical fiber formed of silica-based glass, The optical fiber has a core including a central axis and a cladding surrounding the core. The refractive index of the core is greater than the refractive index of the cladding, The core portion contains chlorine and contains one or more elements selected from the group consisting of alkali metal elements and alkaline earth metal elements. The relative refractive index difference of the core portion based on the refractive index of pure silica is 0.00% or more and 0.15% or less, The average concentration of fluorine in the cladding is 1.2% by mass or less.
2. The optical fiber according to claim 1, wherein The average concentration of fluorine in the cladding is 1.1% by mass or less.
3. The optical fiber according to claim 1, wherein An average concentration of fluorine in a region of the cladding at a distance from the central axis that is not less than 1 time and not more than 2 times the radius of the core is 1.2% by mass or less.
4. The optical fiber according to claim 1, wherein An average concentration of fluorine in a region of the cladding at a distance from the central axis that is not less than 1 time and not more than 2 times the radius of the core is 1.1% by mass or less.
5. An optical fiber formed from silica-based glass, The optical fiber has a core including a central axis and a cladding surrounding the core. The refractive index of the core is greater than the refractive index of the cladding, The core portion contains chlorine and contains one or more elements selected from the group consisting of alkali metal elements and alkaline earth metal elements. The relative refractive index difference of the core portion based on the refractive index of pure silica is not less than -0.15% and not more than 0.05%, The average concentration of fluorine in the cladding is 1.4% by mass or less.
6. The optical fiber according to claim 5, wherein: The average concentration of fluorine in the cladding is 1.3% by mass or less.
7. The optical fiber according to claim 5, wherein: An average concentration of fluorine in a region of the cladding whose distance from the central axis is not less than 1 time and not more than 2 times the radius of the core is 1.4% by mass or less.
8. The optical fiber according to claim 5, wherein An average concentration of fluorine in a region of the cladding at a distance from the central axis that is not less than 1 time and not more than 2 times the radius of the core is 1.3% by mass or less.
9. The optical fiber according to any one of claims 1 to 8, wherein The difference between the maximum value and the minimum value of the residual stress of the optical fiber is 10 MPa or more.
10. The optical fiber according to any one of claims 1 to 8, wherein The effective cross-sectional area of the optical fiber is 70 μm 2 Above and 90μm 2 the following.
11. The optical fiber according to any one of claims 1 to 8, wherein The outer diameter of the cladding is greater than or equal to 124 μm and less than or equal to 126 μm, The residual stress of the optical fiber reaches a maximum value in a region where the distance from the central axis is 20 μm to 55 μm.
12. The optical fiber according to any one of claims 1 to 8, wherein The outer diameter of the cladding is greater than or equal to 124 μm and less than or equal to 126 μm, In the optical fiber, a minimum value of residual stress in a region at a distance from the central axis of 50 μm to 62.5 μm is 10 MPa or less.
13. The optical fiber according to any one of claims 1 to 8, wherein An average concentration of the element in the core portion is 0.2 ppm or more and 200 ppm or less in terms of mass fraction.
14. The optical fiber according to any one of claims 1 to 8, wherein The element group consists of sodium, potassium, cesium and calcium.
Citation Information
Patent Citations
Game machine
JP2019198768A
SiO2-based alkali-doped optical fiber
US5146534A
Alkali and fluorine doped optical fiber
CN101156097A
Large effective area, no Ge core fiber
JP2013518312A
Optical fiber
WO2019172197A1